Finding a voice: reflections on a long journey from silent student to confident teacher educator - Nyamupangedengu, Eunice (South African Journal of Higher Education, 2016)
In this article, I narrate and reflect on challenges that I have faced throughout my academic journey from a school and university student to a teacher and a teacher educator – challenges that I attribute mainly to my limited communicative competence in English. This reflective examination of my experiences is informed by Bourdieu’s cultural capital theory, specifically the concepts of habitus, field and linguistic capital. I argue that the ability to speak, read and write English in my country and in South Africa constitutes linguistic capital and that those who do not possess such capital may have limited access to a country’s desirable goods and positions. Based on what I have experienced, I make some recommendations for recognizing and nurturing student’s home language while at the same time, because English has become such a powerful language locally and globally, creating chances for students to become proficient in this language in order to maximize their opportunities in life.